A Model of Creativity in Organizations: John Holland's Theory of Vocational Choice (1973) at Multiple Levels of Analysis. (4th June 2015) - Sharif, Rukhsar
Abstract: This conceptual paper serves to create a model of creativity and innovation at different organizational levels. It draws on John Holland's Theory of Vocational Choice (1973) as the basis for its structure by incorporating the six different personality types from his theory: conventional, enterprising, realistic, social, investigative, and artistic, as working together with each other within and between teams in organizations. The model begins with opposite personalities working together in two‐person groups to generate creative ideas and then expands to all six personalities working together as one team to implement innovative products and services. It is the underlying contrast of personalities in Holland's (1973) theory, where each personality contributes diverse ideas and skills, that when combined, produce new products and services that are financially beneficial, useful, and enhancing of well‐being for organizations and society.